2021
DOI: 10.3390/molecules26061600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Molecular-Weight Polysaccharides Isolated from Korean Persimmon on the Antioxidant, Anti-Inflammatory, and Antiwrinkle Activity

Abstract: Persimmon (Diospyros kaki), a familiar and widespread fruit worldwide, is known to exhibit several physiological effects because of the presence of pharmacologically active compounds called phytochemicals. However, its high-molecular-weight compounds, particularly polysaccharides, have not been extensively studied. In this study, D. kaki extract (DK) was fractionated into low- and high-molecular-weight fractions (DK-L and DK-H, respectively) through ethanol fractionation, and their effects on antioxidant, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
1
23
2
Order By: Relevance
“…A previous study revealed that the components of DK-L and DK-H had average molecular weights of < 1 kDa and > 345 kDa, respectively. 15 However, in the present study, we found that the molecular weight was 6.7-121.4 kDa and > 1 kDa for FDK-L and 307.3 kDa for FDK-H. As confirmed in a previous study, the present results demonstrated that ethanol precipitation was successfully applied to separate the low-and high-molecular weight fractions of FDK. In addition, the separation by molecular weight allowed the presence of different chemical components in different molecular weight fractions between fermented and nonfermented persimmon fruit to be determined.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…A previous study revealed that the components of DK-L and DK-H had average molecular weights of < 1 kDa and > 345 kDa, respectively. 15 However, in the present study, we found that the molecular weight was 6.7-121.4 kDa and > 1 kDa for FDK-L and 307.3 kDa for FDK-H. As confirmed in a previous study, the present results demonstrated that ethanol precipitation was successfully applied to separate the low-and high-molecular weight fractions of FDK. In addition, the separation by molecular weight allowed the presence of different chemical components in different molecular weight fractions between fermented and nonfermented persimmon fruit to be determined.…”
Section: Discussionsupporting
confidence: 85%
“…In our previous study, the chemical composition of DK-H included total sugar, uronic acid, and polyphenol at 460.6, 436.9, and 109.6 mg g −1 , respectively. 15 When comparing DK-H and FDK-H, we conclude that the fermentation of persimmon fruit extract led to a significant increase in total sugar content by more than 200 mg g −1 , while uronic acid content decreased as the total sugar content increased. The results indicate that a significant change in molecular patterns was induced by traditional fermentation of persimmon fruit.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations